Hormonal consequences of missing the pill during the first two days of three consecutive artificial cycles - Landgren, B M; Diczfalusy, E (Contraception (Stoneham), 1984)
The hormonal effects of the deliberate omission of a low-dose combined oral contraceptive pill (30 micrograms ethinyl estradiol + 150 micrograms levonorgestrel) during the first two days of three consecutive artificial cycles were studied in 10 women. The plasma levels of estradiol, progesterone, levonorgestrel and--whenever justified--of LH were measured three times weekly (Mondays, Wednesdays and Fridays) throughout a 90-day period, and the ovarian reaction to the prolongation of the pill-free period from 7 to 9 days was assessed. One subject (with a premature LH surge) showed a marked follicular and an inadequate luteal activity in 2 of 3 cycles. The remaining cycles were characterized by a varying degree of follicular activity associated with the absence of any luteal function. None of the subjects exhibited peripheral steroid levels indicating a normal ovulatory cycle. The results are interpreted as suggesting that repeated prolongation of the pill-free period from 7 to 9 days might result in a gradual increase in ovarian activity.